Evaluating the bone‐regenerative role of the decellularized porcine bone xenograft in a canine extraction socket model - Yuan‐Wu Chen; Meng‐Yen Chen; Dar‐Jen Hsieh; Srinivasan Periasamy; Ko‐Chung Yen; Chao‐Tang Chuang; Hung‐Chou Wang; Fan‐Wei Tseng; Jer‐Cheng Kuo; Hua‐Hong Chien (Wiley, 2021)
Abstract Objective To evaluate the efficacy of a novel decellularized porcine bone xenograft, produced by supercritical carbon dioxide extraction technology, on alveolar socket healing after tooth extraction compared to a commercially available deproteinized bovine bone (Bio‐Oss®). Materials and methods Nine dogs (about 18 months old and weighing between 20 kg and 30 kg) underwent extractions of lower second to fourth premolars, bilaterally. The dogs were randomly selected and allocated to the following groups: Group 1: control unfilled socket; Group 2: socket filled with decellularized porcine bone xenograft (ABCcolla®) and covered by a commercially available porcine collagen membrane (Bio‐Gide®); Group 3: socket filled with Bio‐Oss® and covered by Bio‐Gide® membrane. One dogs from each group was sacrificed at 4‐, 12‐, and 24‐week to evaluate the socket healing after tooth extraction. The mandible bone blocks were processed without decalcification and specimens were embedded in methyl methacrylate and subjected to histopathology analyses to evaluate the bone regeneration in the extraction sockets. Results At 24‐week after socket healing, ABCcolla® treated defects demonstrated significantly higher histopathology score in new bone formation and bone bridging, but significantly lower score in fluorescent labeling than those of the Bio‐Oss®. In the microphotographic examination, decellularized porcine bone xenograft showed similar characteristics of new bone formation to that of Bio‐Oss®. However, there was significantly less remnant implant materials in the decellularized porcine bone xenograft compared to the Bio‐Oss® group at 24‐week. Thus, the decellularized porcine bone graft seems to have promising bone regeneration properties similar to that of Bio‐Oss® with less remnant grafted material in a canine tooth extraction socket model. Conclusions Within the limits of the study, we concluded that ABCcolla® treated defects demonstrated significantly more new bone formation and better bone bridging, but less amount of fluorescent labeling than those of the Bio‐Oss® group. However, clinical studies in humans are recommended to confirm these findings.